Socio-economic perspective of informal vendors in Chapinero: Bogotá, Colombia - Rincón Báez, William Umar; Soler Hurtado, Andrea Johanna (Cooperativismo & Desarrollo, 2016)
Introduction: Informal sales in Bogota have increased due to the serious unemployment situation the country is going through. Methodology: This research is descriptive and sought to socio-demographically characterize the sample and determine the economic factors of the business and the financial products used by street vendors in the locality of Chapinero in Bogota, Colombia. As a technique, simple random sampling was used with a survey endorsed by three judges. Results: It was found that policies have been inefficient, thus creating different problems. Conclusions: Unemployment, as well as lack of resources and access to loans as seed capital, give rise to factors that, linked to the social problem, find in informal work a form of subsistence. Generally, the same problem is detected in Bogota, especially in Chapinero for being a financial and commercial sector, which provides favorable conditions to promote and multiply informal work. It is shown how informal vendor relocation policies implemented by different district administrations have been unfruitful.